The Effect of Tax Uncertainty, Stock Market Liquidity, Earnings Management on Firm’s Investment - Ichsan, Dinul; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2017)
Abstract – Lack of transportation modes in the Papua region causing difficulties for people and entrepreneur in the ordinary course of business. Therefore, it needs the support and participation ofthe government to develop the area. One of these fuel prices are quite high in rural areas of Papua. PT. Pegasus Air Services will participate in the government program for the 'flying tanker' so that the price of fuel can be reduced by 50% and the community in the mountains of Papua can be purchased at an affordable price. Plans for the acquisition of air cargo is one form of program that should be done by the management of PT. Pegasus Air Services in an effort to develop a market along business lines so as to create increased revenue. Management has appointed the manager on duty related to the selection process on which the manufacturer and the type of aircraft is the most effective and efficient. The company has invited representatives of the aircraft manufacturer to be able to submit their proposals. After receiving the documents and all the necessary information, the Managers will further provide advice and recommendations to the management of PT. Pegasus Air Services on which the manufacturer along with the type of aircraft to be acquired and explain why and how the decision been to these manufacturers. Previously, the manager also has set some criteria that will be used to evaluate the plan acquisition of a cargo plane and also perform the weighting of each of these criteria in the decision making process. This final project will explain the process of selecting the cargo aircraft acquisition plans undertaken by PT. Pegasus Air Services. The information contained in this final project will also be usefulfor the parties who have an interest and / or the needs of the decision making process for the procurement of cargo planes in their company.Keywords: Acquisition Plan, PT. Pegasus Air Services, Cessna Caravan, Quest Kodiak, Decision Making Process